EFFECTIVENESS OF PROVIDING EDUCATION ON THE ANXIETY OF PATIENTS WHO WILL HAVE PCI PROCEDURES IN THE EMERGENCY ROOM AT HARUM SISMA MEDIKA HOSPITAL IN 2023 - Lestari, Ketut Ayu; Khamid, Abdul (HEARTY, 2025)
Background: Cardiovascular disease is the main cause of death throughout the world. The World Health Organization (WHO) states that every year deaths due to cardiovascular disease reach more than 17.8 million. Meanwhile, data from the Indonesian Ministry of Health in 2023 in Indonesia the death rate due to this disease will reach 650,000 people per year. Coronary heart disease is a type of cardiovascular disease. Coronary heart disease patients require Percutaneous Coronary Intervention (PCI) to improve their quality of life. Providing clear and complete information to patients is an effective intervention in increasing patient knowledge, reducing their symptoms of anxiety and fear. Nurses have an important role in health education for patients. Based on the results of a preliminary study at Harum Sisma Medika Hospital, data on the number of cases of patients with Coronary Heart Disease (CHD) in 2023 from January to October reached 256 and those referred out for Percutaneous Coronary Intervention (PCI) in the Emergency Room at Harum Hospital numbered 35 patients. And on average, these patients experience anxiety or anxiety when they are informed that Percutaneous Coronary Intervention (PCI) will be carried out. Purpose of writing: To determine the effect of providing education on the anxiety of patients who will undergo Percutaneous Coronary Intervention (PCI) in the emergency room at Harum Sisma Medika Hospital, Jakarta. Writing Method: The research method used in this research is Pre Experimental Design. This research used a Quasi Experimental design using the "Pre-Test and Post-Test" method with a sample of 55 respondents. Research Results: The results of this study show that before and after the intervention of providing education on the anxiety of patients who will undergo percutaneous coronary intervention (PCI) in the emergency room at Harum Sisma Medika Hospital, Jakarta, a P value of 0.001 < 0.05 is obtained, which means providing education to patients who will Percutaneous Coronary Intervention (PCI) in the emergency room at Harum Sisma Medika Hospital, Jakarta, was effective in reducing anxiety levels in respondents. Conclusions and Suggestions: There is a significant influence on providing education to patients who will undergo Percutaneous Coronary Intervention (PCI) to reduce anxiety before undergoing Percutaneous Coronary Intervention (PCI). It is recommended that all health workers, especially nurses, provide education before carrying out Percutaneous Coronary Intervention (PCI).